Public disclosure for carbon abatement: African decision-makers in a PROPER public good experiment. (19th September 2017) - Akpalu, Wisdom; Abidoye, Babatunde; Muchapondwa, Edwin; Simbanegavi, Witness
Abstract : A linear public good experiment adopted from Holt and Laury [1997. Classroom games: Voluntary provision of a public good. Journal of Economic Perspectives, 11(4), 209–215.] has been employed to investigate strategic behaviour in pollution abatement among African climate decision-makers. The experiment consisted of three groups, of which groups 2 and 3 received one and two treatments, respectively. The first treatment entailed publicly disclosing the pollution of each member of a group by placing a corresponding colour-coded card in front of each subject, while the second involved the withdrawal of the public disclosure. Group 2 received the first treatment; Group 3 received both the first and second treatments in succession. We found that the untreated group (baseline) polluted more than the two treated groups, and there was no statistically significant difference between the pollution abatement of the two treated groups. These results suggest that public disclosure potentially drives pollution abatement and that its eventual withdrawal does not obliterate abatement behaviour. We did not observe conditional cooperation but average pollution declined over time. Furthermore, individuals who thought it was unfair for Africa to reduce emissions polluted more. We also found that pollution levels differ significantly between males and females.